2020
DOI: 10.3389/fphar.2020.542902
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Is the Target Gene for 2,3,5,4’-Tetrahydroxystilbene-2-O-β-D-Glucoside Alleviating the HUVEC Senescence

Abstract: This study aimed to explore the effects of 2,3,5,4'-tetrahydroxy-stilbene-2-O-b-dglucoside (TSG) on the senescence of human umbilical vein cells (HUVEC) induced by hydrogen peroxide (H 2 O 2) and to identify the potential targets mediating its protective action. HUVEC cells pre-treated with TSG for 24 h were exposed to H 2 O 2 treatment. TSG significantly decreased H 2 O 2-induced cellular senescence, as indicated by reduced senescence-associated b-galactosidase (SA-b-gal) positive staining, the proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been reported that chondrocyte senescence could be mediated by IL-1β treatment via the p53/p21/pRb pathway, with the induction of caveolin 1 and activation of p38 mitogen-activated protein kinase (MAPK), resulting in cell senescence and apoptosis (32). Moreover, researchers have revealed that the expression levels of PAI-1 and p21 proteins have a positive correlation with the presence of SA-β-gal (2,33). PAI-1 is a member of the evolutionarily conserved serine protease inhibitor (SERPIN) family and is well known as a marker and mediator of senescence, revealed by its increased expression in senescent cells (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chondrocyte senescence could be mediated by IL-1β treatment via the p53/p21/pRb pathway, with the induction of caveolin 1 and activation of p38 mitogen-activated protein kinase (MAPK), resulting in cell senescence and apoptosis (32). Moreover, researchers have revealed that the expression levels of PAI-1 and p21 proteins have a positive correlation with the presence of SA-β-gal (2,33). PAI-1 is a member of the evolutionarily conserved serine protease inhibitor (SERPIN) family and is well known as a marker and mediator of senescence, revealed by its increased expression in senescent cells (34,35).…”
Section: Discussionmentioning
confidence: 99%